Effects of dietary supplementation with fermented Astragalus membranaceus on growth performance, antioxidant capacity and intestinal barrier function of common carp (Cyprinus carpio) - Han, Yingqian; Ma, Baocai; Wangshao, Mingyu; Wang, Xiufen; Guo, Jianxun; Su, Xiaoying; Guo, Shuang; Yang, Guoyu; Pan, Jiajia; Shi, Hongtao (Frontiers in Immunology, 2025)
IntroductionOxidative stress hinders the growth and intestinal function of aquatic animals, reducing aquaculture profits. While Astragalus membranaceus (AM) is known for its antioxidant properties, its low bioavailability is a drawback. Probiotic fermentation can enhance AM’s pharmaceutical efficacy. This study aimed to assess the effects of various probiotic-fermented AM preparations on the growth performance, antioxidant activity, and intestinal health of common carp.MethodsA total of 225 common carp (44.70 ± 1.42 g) were allocated into five groups with three replicates for an 8-week experimental trial. During the experiment, the control group fish were provided with a basal diet. The test groups of fish were fed a basal diet supplemented with 1‰ Lactobacillus plantarum-fermented AM preparation, 1‰ Saccharomyces cerevisiae-fermented AM preparation, 1‰ Bacillus subtilis-fermented AM preparation, or 1‰ combined fermented AM preparation.Results and discussionThe findings demonstrated that supplementation with fermented AM preparations significantly improved the final body weight, weight gain rate, specific growth rate, and feed protein efficiency of common carp, while markedly decreasing the feed conversion ratio (p < 0.05). Furthermore, there was a notable enhancement in serum antioxidant activity and immune responses, evidenced by increased levels of superoxide dismutase, catalase, glutathione peroxidase, lysozyme, and phagocytic activity (p < 0.05), alongside reduced levels of malondialdehyde (p < 0.05). The supplementation also improved intestinal health by enhancing intestinal barrier function, as indicated by the stimulation of the PI3K/AKT/mTOR signaling pathway, which led to increased expression of tight junction proteins (p < 0.05). Additionally, it promoted the formation of the intestinal mucus layer, increased the secretion of lysozyme and alkaline phosphatase (p < 0.05), activated the Nrf2 signaling pathway to upregulate antioxidant-related genes (p < 0.05), and inhibited the TLR4/MyD88/NF-κB signaling pathway, thereby reducing pro-inflammatory responses. These findings indicate that fermented AM preparations can improve the antioxidant potential and immune functions, thus promote the growth of common carp.